Novel security Image Steganography Based on DWT and Pseudorandom Sequences - Talib Hussein, Refat; A. Jafar, Awatf (Journal of Engineering and Sustainable Development, 2010)
In this paper, a new technique that address the problem of high capacity and data security in steganography is proposed. A robustness system is achieved by choosing a transform domain technique for embedding. The proposed system is based on the idea of the wavelet based fusion. In this method the wavelet decomposition of the cover image and the secret image are merged into a single result called stego-image. High security system is achieved by generation of three PN-sequences; one to encrypt the secret image and the others to choose the position of embedding. The quality of the stego-image is very close to that of the original one and the recovered image is similar to the hidden secret image (Corr.≈1).